Analysis of Fiduciary Guarantee Items Transmitted by Debtors from a Legal Perspective - Dahris Siregar (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2025)
The demand for finance rises in tandem with the expansion of development activities, and the majority of the money required to satisfy these needs may be acquired through borrowing and borrowing activities, one of which is through financial institutions' services. This study aims to determine the status of the debtor transferred in accordance with the terms of the agreement, ac-cording to the fiduciary guarantee object. and to find out about the credit settlement attempts that the debtor made. Normative juridical research methodology is employed in the scientific study of fiduciary guarantee law. The study's findings indicate that in order to ascertain the legal standing of the fiduciary guarantee object that the debtor transferred, registration is necessary. This gives the creditor legal certainty regarding the fiduciary guarantee object's legal position, and negotiations with the debtor and other parties who consent to the transfer of the fiduciary guarantee object are used to carry out credit settlement activities. The result shows that because the fiduciary guarantee object transmitted by the debtor only registers a portion of the fiduciary promise, it has a weak legal standing, allowing the debtor to transfer the unregistered fiduciary guarantee object. In an attempt to replace the collateral that was transferred to a third party with an item that belongs to the debtor and has a value equal to the transferred collateral, creditors have applied dispute resolution through a non-litigation settlement method that involves negotiation and mediation between the parties.